2012
DOI: 10.1542/peds.2011-2581
|View full text |Cite
|
Sign up to set email alerts
|

Background Television in the Homes of US Children

Abstract: OBJECTIVE: US parents were surveyed to determine the amount of background television that their children are exposed to as well as to isolate demographic factors associated with increased exposure to background television. After this, we ask how certain home media practices are linked to children’s background television exposure. METHODS: US parents/caregivers (N = 1454) with 1 child between the ages of 8 months and 8 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 31 publications
5
87
1
3
Order By: Relevance
“…However, children' s media environments are constantly changing, and limitations of this study include its lack of measures of background TV or mobile media, both highly prevalent in children' s lives, 18,34 and reliance on parental report, which is subject to more bias than use of a media diary. Our categorical outcome (.2 hours per day) was relatively common in this cohort, so use of odds ratios, although valid, may overestimate the true relative risks associated with poor selfregulation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, children' s media environments are constantly changing, and limitations of this study include its lack of measures of background TV or mobile media, both highly prevalent in children' s lives, 18,34 and reliance on parental report, which is subject to more bias than use of a media diary. Our categorical outcome (.2 hours per day) was relatively common in this cohort, so use of odds ratios, although valid, may overestimate the true relative risks associated with poor selfregulation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how masked speech perception develops is important because infants must learn about speech and language in natural environments that often contain multiple sources of competing sounds. For instance, a number of studies have shown that infants tend to spend more time in environments containing competing sounds than they do in quiet (e.g., van de Weijer 1998; Barker and Newman 2004; Lapierre et al 2012; Ambrose et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Background TV refers to adult media content that is on while children are in the room but is unintelligible to them (Lapierre, Piotrowski, & Linebarger, 2012). Parents can often leave the TV on in the home regardless of whether someone is watching it or not (Parenting in the Age of Digital Technology: A National Survey, 2013; Roberts & Foehr, 2004).…”
Section: The Impact Of Background Tv On Child Outcomesmentioning
confidence: 99%
“…Parents can often leave the TV on in the home regardless of whether someone is watching it or not (Parenting in the Age of Digital Technology: A National Survey, 2013; Roberts & Foehr, 2004). According to Lapierre, Piotrowski, and Linebarger (2012), on average, US children are exposed to 232.2 minutes of background TV on a typical day. Research has found that rapid visual and auditory changes can distract young children from exploration and toy playtime as their attention is directed towards the screen numerous times during a play session (Schmidt, Pempek, Kirkorian, Lund, & Anderson, 2008).…”
Section: The Impact Of Background Tv On Child Outcomesmentioning
confidence: 99%